Chemobrionic Fabrication of Hierarchical Self‐Assembling Nanostructures of Copper Oxide and Hydroxide. Issue 3 (2nd August 2019) - Escamilla‐Roa, Elizabeth; Cartwright, Julyan H. E.; Sainz‐Díaz, C. Ignacio
Abstract: Copper oxide nanostructures have great potential use in a plethora of nanotechnology applications including nanoelectronics, photovoltaics, sensors, electrochemistry, and pharmacology. In the present work we show how hierarchically nano‐structured copper oxide and hydroxide may be prepared through self‐assembly from CuSO4 salt and silicate solutions using the chemobrionic growth process of a chemical garden. Procedures were explored using the cupric salt in either solid (pellet and seed growth methods) or liquid phase (fluid injection techniques). Self‐assembling nanostructures were characterized by means of environmental scanning electron microscopy (ESEM) with energy‐dispersive X‐ray spectroscopy (EDX) analysis, micro‐Raman spectroscopy and X‐ray diffraction. Our results show the formation of crystalline aggregates of copper oxide and hydroxide in complex hierarchical nanostructured forms including fans, flowers, petals, skeins, lentils, and sheaves. Analytical methods corroborate that these nanostructures may be selected in shape and chemical composition with the reaction conditions. Abstract : Chemical gardens : Hierarchically nanostructured copper oxide and hydroxide may be prepared through self‐assembly from CuSO4 salt and silicate solutions using the chemobrionic growth process.